Ibuprofen removal through photocatalytic filtration using antifouling PVDF- ZnO/Ag2CO3/Ag2O nanocomposite membrane - Rosman, Nurafiqah; Wan Salleh, Wan Norharyati; Mohd Razali, Nur Aqilah; Ahmad, Siti Zu Nurain; Ismail, Nor Hafiza; Aziz, Farhana; Harun, Zawati; Ismail, Ahmad Fauzi; Yusof, Norhaniza (Elsevier, 2021)
The in-situ phase transformation of Ag2CO3/Ag2O heterojunction over ZnO was synthesized via a facile two-step synthesis method and immobilized in poly (vinylidene fluoride) (PVDF) membrane via a phase inversion process to obtain a novel photocatalytic membrane (PM) for ibuprofen (IBU) removal. The visible-light-driven PVDF ZnO/Ag2CO3/Ag2O membrane possessed a great extent altering its morphological and wettability properties. The structural characteristics and antifouling property of PMs with the presence of ZnO/Ag2CO3/Ag2O were systematically investigated. The performance analysis indicated that PVDF–ZnO/Ag2CO3/Ag2O showed a higher IBU percentage removal of 27.37% in dark condition. However, as the PVDF–ZnO/Ag2CO3/Ag2O membrane irradiated with visible light, the synergistic effects accomplished by both, membrane filtration and photocatalysis have significantly enhanced the IBU removal efficacy compared with that via filtration alone, exhibited 35.27% of IBU removal. The photocatalytic activity has remarkably reduced the fouling susceptibility of PVDF–ZnO/Ag2CO3/Ag2O membranes, where the relative flux had reached a relative stable plateau under visible light irradiation after the collection of 150 mL of permeate with 46.85% of flux loss. With its promising performance in terms of IBU removal, flux and low membrane fouling susceptibility, this PM holds great potential for its application in pharmaceutical wastewater treatment.